The profiles of science and technology culture (STC) indicators - A. Halim (Syiah Kuala University, 2013)
Culture of science and technology is the way of life of the academic community that includes ways of thinking, understanding and use of technology, beliefs, habits, how to use the language, attitudes, and judgments based on scientific methods and knowledge. Survey of 10 indicators of science and technologyculture conducted to 467 high school students in Indonesia and 784 students in Malaysia. Based on 10 indicators, developed an instruments of Likert attitude scale and a multiple choice tests as a basis for indicators of science and technology culture. The survey results showed that students SM Malaysia andIndonesia have the same ability and views about; Knowledge of Science and Technology Basic, Understanding the limitations of human reason, and understanding of science and technology indicators, and the student chooses more amenable Science and Technology activities conducted outside school hours. Overall, the profiles of Science and Technology culture among students SM SM Indonesia Malaysia and there is no significant difference at the 1% significance level (t = 0:04). Based on the interpretation of the scalesuggested by Green Akey, the results of this study showed that the culture of Science and Technology indicators proposed in this study include both categories, namely 0.75 (high) Indonesian and 0.74 (high) Malaysian. Therefore it can be said that Malaysian and Indonesian students have a positive attitude towards Science and Technology. In the context of the Science and Technology Education, the results of this study provide some indicators that can be used as learning objectives in the curriculum of Science and Technology in the Secondary School